Playing the self-adventure board game to increase adolescents' self-esteem - Desi Desi; Fiane de Fretes; Rosiana Eva Rayanti; Marsela Riska Raswandaru (Universitas Muhammadiyah Magelang, 2024)
Competition in the field of education to become excellent, accredited, and favored has an impact on students. Indirectly, to maintain their ranking status, schools generally design various dense academic and non-academic programs, requiring students to give special attention and energy. On the other hand, parents nowadays also tend to have a competitive spirit burdened on their children. One age group particularly susceptible to this situation is teenagers. Exposure to pressure inversely proportional to students' abilities will result in them experiencing low self-esteem (LSE), which if left unaddressed, can lead to depressive and even suicidal conditions. To address LSE, a therapy called